Colorless polyimides derived from isomeric dicyclohexyl-tetracarboxylic dianhydrides for optoelectronic applications. (3rd January 2018) - Hu, Xiaofan; Mu, Hongliang; Wang, Yongxia; Wang, Zhen; Yan, Jingling
Abstract: Two isomers of conventional cis -dicyclohexyl-3, 3′, 4, 4′-tetracarboxylic dianhydride (4, 4′-HBPDA), i.e. dicyclohexyl-2, 3′, 3, 4′-tetracarboxylic dianhydride (3, 4′-HBPDA) and dicyclohexyl-2, 2′, 3, 3′-tetracarboxylic dianhydride (3, 3′-HBPDA), were prepared through a four-step procedure. The data from single crystal X-ray diffraction revealed that 3, 3′-HBPDA possessed higher structural rigidity/linearity than 4, 4′-HBPDA. The one-step polycondensation of isomeric HBPDAs with commercial diamines enabled the synthesis of alicyclic polyimides. The isomer effects of the dianhydrides on the properties of resulting polyimides were studied in detail. For certain diamines, 3, 3′-HBPDA-derived polyimides possessed higher glass transition temperatures ( T g ) and better dimensional stability compared with those from 4, 4′-HBPDA and 3, 4′-HBPDA. These phenomena could be attributed to the higher structural rigidity/linearity of 3, 3′-dicyclohexyl-tetracarboxydiimide, and restricted rotation of 3-substituted cyclohexylimide. Owing to the asymmetric structures and suppressed rotation of 3-substituted cyclohexylimides, 3, 4′-HBPDA-based polymers exhibited higher T g, improved dimensional stability, and enhanced solubility compared with 4, 4′-HBPDA-based ones. Furthermore, all the isomeric HBPDA-derived polyimides were essentially colorless with excellent optical transparency in the UV–Visible region. The excellent overall properties of polyimides from 3, 3′-HBPDA and 3, 4′-HBPDA made them promising candidate materials for optoelectronic applications. Graphical abstract: Image 1 Highlights: Two novel alicyclic dianhydrides, 3, 4′-HBPDA and 3, 3′-HBPDA, were successfully synthesized through a four-step procedure. Single-crystal X-ray diffraction results showed that 3, 3′-HBPDA had higher structural rigidity/linearity than 4, 4′-HBPDA. 3, 3′-HBPDA-based polyimides exhibited higher T g and dimensional stability compared with those based on 4, 4′-HBPDA. 3, 4′-HBPDA-based polyimides showed higher T g, lower CTE, and improved toughness and solubility than 4, 4′-HBPDA-based ones. The isomer effects of the dianhydrides did not significantly impact the optical properties of the resulting polyimides.